THE PSYCHOLOGICAL DIAGNOSTIC ASSESSMENT OF CHILDREN-VICTIMS OF SEXUAL VIOLENCE - Kozlova, Anna (PSYCHOLOGICAL JOURNAL, 2020)
The article examines the features of children’s psychological trauma appeared because of sexual violence. The author presents theoretical definitions for the concepts of “violence”, “sexual violence”, “sexual violence against children” based on the performed scientific review; these definitions have become basis for the assessing protocol for children-victims of sexual violence. Particular attention is paid to the definition of “psychological trauma” and its features. The author derived main features that allow her characterize children with psychological traumas because of sexual abuse. The article author presents her own theoretical provisions for “psychological trauma”, the stages of a child’s experiences of a psychologically traumatic situation to assess the signs of psychological traumas at children suffered of sexual violence. Based on the understanding of the concept of “sexual abuse of children”, “psychological trauma” and the dynamic of a psychological trauma, in particular, its stages, the signs of psychological traumas at children suffered sexual violence were developed. The author’s approach to psychological diagnostics is described: the study organization, evaluation of criminal proceedings materials, special interview and its further evaluation by the criteria. Based on the conducted psychological diagnostic research, a protocol assessing the signs of psychological traumas at children appeared because of sexual violence was developed. It contains three assessment blocks: assessment of a child’s life and health, the characteristics of a psychological trauma and the peculiarities of understanding by the child of sexual violence. The article presents the results of our own examination of children-victims of sexual violence aged 4 to 10 years. Based on this examination the effectiveness of the assessment protocol was assessed, thus the proposed protocol objectively assesses an individual impact of sexual violence on an examined child. The protocol for psychological diagnostic assessment of children-victims of sexual violence allows psychologists to create structured written opinions in the framework of forensic or expert examinations.